Market Potential of Oriented Strand Board (OSB) & Laminated OSB (Lami-OSB) in Asia Pacific - Yoong, Hau Chun (2001)
With the recent reduction in local forest concessions and environmental issues worldwide, logs supply are limited and have to be purchased at a higher premium. Therefore, the use of plywood and sawn timber are no longer viable. One solution to this is to use OSB as an alternative. OSB is a structural panel suitable for a wide range of construction and industrial applications. OSB has gained tremendous market share in the North America and popularity is also now booming in Europe, and the Asia Pacific is seen as the next region with the great potential for OSB product development. This thesis provides an insight to OSB and Lami-OSB, and further explores into the potentials of these products on how it could be accepted in the Asia Pacific region as a new structural panel commodity product.